Influence of CaZrO3 nanocrystals on phase structure, microstructure and electrical properties of BCZT ceramics prepared by seed-induced method - Hirunsit W. (2017)
Copyright © 2017 American Scientific Publishers. In this study we report phase structure, microstructure and electrical properties of lead-free piezoelectric ceramic prepared by seed-induced method. The seed-induced method is a technique that uses nanocrystal to improve phase structure of perovskite. The seed provide a framework for anisometric BCZT grain to form around the seed. Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 (BCZT) ceramic system was doped with CaZrO 3 (CZ) seed (0-10 mol%) which is prepared via the mixed oxide method. The mixed powders were calcined at 1200 °C for 2 hours and sintered at 1400 °C for 4 hours. The CZ-seed was prepared by the molten salt method. The results showed that dense ceramics with pure perovskite phase were obtained for all samples. Density and average grain size values were in the range of 5.37-5.53 g/cm 3 and 5.53-8.48 °m, respectively. The sample with at 10 mol% seed exhibited a value of dielectric constant (ϵr ) of 12265 at optimum temperature and excellent piezoelectric performance with high piezoelectric coefficient of 477 pC/N. The CZ-seeds doped BCZT ceramics could be promising candidates as lead-free piezoelectric materials.